Independent risk factors for chronic cyclosporine induced nephropathy in children with nephrotic syndrome. Issue 8 (2nd May 2006) - Fujinaga, S; Kaneko, K; Muto, T; Ohtomo, Y; Murakami, H; Yamashiro, Y
Abstract : Background: Cyclosporine A (CsA) has been widely used in children with steroid dependent and steroid resistant nephrotic syndrome (NS) because of its efficacy in relieving these patients from systemic side effects of steroids. However, its long term use is controversial, since chronic CsA induced nephropathy (CsAN) may develop in a considerable number of patients. Aims and Methods: In order to clarify the risk factors for the development of CsAN, the clinical characteristics of children with steroid dependent or steroid resistant NS taking CsA (target blood trough levels 50–150 ng/ml) for more than six months, managed at a single centre, were retrospectively analysed. Results: Thirteen of 30 children (24 boys and 6 girls) taking CsA (mean duration 43 months, range 6–144) had CsAN defined as the presence of CsA associated arteriopathy with or without striped tubulointerstitial lesions. The multivariate analysis revealed that CsA treatment for more than 36 months and an age younger than 5 years at the start of CsA treatment were independent risk factors for the development of CsAN. The univariate analysis also showed that patients with CsAN had more frequent relapses during CsA treatment than those without CsAN. Conclusion: An alternative treatment should be seriously considered after a 36 month administration of CsA in order to prevent CsAN. Data also suggest that CsA treatment in children younger than 5 years should be avoided if possible.